Pengaturan Undang-Undang Darurat Nomor 7 Tahun 1955 dalam Rangka Pemberantasan Kejahatan Ekonomi di Indonesia - Afdhali, Dino Rizka; Prasetyo, Handoyo (CV. Era Digital Nusantara, 2024)
Economic crime is a new dimension of crime, the perpetrators of which consist of wealthy, intellectual and organized groups. Economic crime is also called white collar crime. Another characteristic of this crime is seen from its high mobility and is carried out not only in one region, but also across national borders. This article aims to explain the meaning and scope of economic crime, define the characteristics of economic crime and determine the regulation of economic crime in the Indonesian legal system. Based on the research, it was found that economic criminal law is part of the criminal law that has its own characteristics, namely the economic character with a very broad scope, including: smuggling, banking crimes, commercial crimes, cyber crimes, environmental crimes, digital economic crimes, crimes in the field of intellectual property rights, corruption, crimes in the field of labor and others. The research method used uses a normative legal approach. The purpose of this study is to determine the efforts of the Indonesian government in implementing regulations related to cases of economic violations in order to realize the eradication of economic crime in Indonesia. The research results state that as a special criminal law, the law governing economic violations certainly has a strong theoretical basis. Economic criminal law has special provisions contained in the field of substantive criminal law and criminal procedure law. Economic crimes are regulated in Emergency Law Number 7 of 1955 concerning the investigation, prosecution and trial of economic crimes.